Determinants of leverage and regulation: an analysis in dental health plan operators - Avelar, Ewerton Alex; Souza, Antônio Artur de; Amaral, Hudson Fernandes; Orefici, Jacqueline Braga Paiva; Cailleau, Romain (Revista de Administração da UFSM, 2020)
Purpose – This paper examines the determinants of debt levels of Brazilian dental health plan operators (OPS) under the National Supplementary Health Agency (ANS) regulation. Design/methodology/approach – It is an empirical article based on quantitative and causal research. The sample consisted of data from 2010 to 2018 available on the ANS website. The techniques of content analysis, descriptive statistics and panel regression were used for data analysis. Findings – We found that several variables related to the ANS regulation influence dental OPS debt levels. Furthermore, there are also several similarities between the two categories under analysis: dental cooperatives and group dentistry, despite the differences in the legal nature of such organizations. Research limitations/implications – The present study suffers from some limitations: (a) the sample investigated is restricted to OPS public data; and (b) regulation variables are limited due to the data available for calculation, despite our efforts to show otherwise. Originality/value – The present research offers a range of contributions to the literature on dental operators’ capital structure. Firstly, it emphasized the impact of regulation in dental operators’ financial decisions in Brazil. Moreover, it confirmed the important role of companies’ determinant variables of capital structure in explaining OPS debt levels. Lastly, the study introduced regulatory variables as determinants of OPS debt ratios.